Upaya Pencegahan Kasus Cyberbullying bagi Remaja Pengguna Media Sosial di Indonesia - Rahmat Syah; Istiana Hermawati (Jurnal Penelitian Kesejahteraan Sosial, 2018)
This research aims to analyze about cyberbullying that covers the definitions, types, motives, impacts, and the prevention efforts. This was a was using literature research with a qualitative descriptive approach. The data was collected by conducting secondary data documentation which sourced from data of survey institution, special cases on related topic from update news, and research studies. Cyberbullying is a threat contributing to mental, psychological and social disorders. The causal factors of bullying are family, school and peers. In fact, the victims of cyberbullying may be treated as early as possible by involving parents, teachers and school environment, and peers. The recommendations from this study are 1) to the parents: they should take more time with their children, pay attention to their activities in social media, recognize and help to develop their interest and talent, imbed moral values to them by setting good examples in family. 2) to the Government: Children Social Rehabilitation General Directorate of Indonesia Social Ministry is suggested to hold counseling activities to parents and teachers on ways of overcoming cyberbullying, enhance the social workers role and their capacities in accompanying the victims, to provide special guidelines for parents on preventing their children against cyberbullying, to work together with related institutions to set up comprehensive laws and regulations accordingly 3) to teachers: to provide proper direction to their students of how to use the internet in positive way, to optimize environmentbased healthy activities, to enhance the performance of guidance and counseling teachers by monitoring and conducting students’ self-assessment.